Excavations in the legionary fortress of Brigetio in 2019 - Bartus, Dávid; Borhy, László; Joháczi, Szilvia; Számadó, Emese (Dissertationes Archaeologicae, 2021)
In 2019 the excavations in Brigetio focused on the area of the northern gate of the legionary fortress, as the geophysical surveys conducted in the previous year allowed the identification of both the porta praetoria and the via praetoria leading through it. These fieldworks, beside providing new information on the topography of the legionary fortress regarding the porta praetoria and the via praetoria, were also significant from a methodological point of view as they allowed the verification of the results of geophysical surveys conducted in the area earlier, thus contributing greatly to the planning and fine-tuning of future measurements.